V-Chips Enterprise / Myron Jemut ... [et al.] - Jemut, Myron; Bagah, Casey Brent; Hamilin, Faten Nadia; Omar, Latipah; Rasid, Surianti (2009)
We are known as V-Chips Enterprise whereby our main product is 'Kerepek Bayam'. We are located at Kg. Malangang Baru, Tamparuli. We are producing and supplying our products mainly around Kota Kinabalu area. We want to develop an existing product which is 'Kerepek Bayam' by adding two new flavors; spicy and sweet. V-Chips 'Kerepek Bayam' made from spinach leaves and without MSG (Monosodium Glutamate), which makes our product special and different from the existing one. Our product is made 100% plant based which is spinach that rich in benefits such as;